Analisis Kebutuhan Pelatihan untuk Pengembangan Kompetensi Pelaku UMKM (Studi di Lembaga Perekonomian Nahdlatul Ulama Pamekasan) - Moh. Afnan Rahmaturrahman (Universitas Airlangga, 2022)
This study aims to analyze the training needs for competency development of MSMEs assisted by the Lembaga Perekenomian Nahdlatul Ulama Pamekasan. This research uses an interpretative qualitative descriptive design based on applied research. Research data were obtained by in-depth interviews and the use of secondary data in the form of documents. Informants consisted of LPNU Pamekasan administrators and assisted MSMEs. The interviews were then transcribed and analyzed by organizing the data, reducing the rough data, presenting the data (display data), and interpreting the results and drawing conclusions. The results of this study reveal that there is a lack of competence of MSME actors and requires training content consisting of aspects of marketing, production and financial management. The training delivery method can be done in the form of online training, informal discussions, and workshops. Â Keywords: MSMEs, training, competency, training needs analysis